Empowering lower status workers in long -term care: The impact of including CNAs and LPNs in interdisciplinary team meetings on their levels of turnover, stress, coping, and self -esteem - Torsney, Kathleen Marie (ProQuest Dissertations & Theses, 2000)
The purpose of this study was to investigate the impact of including certified nursing assistants (CNAs) and licensed practical nurses (LPNs) in interdisciplinary team meetings at a long-term care facility on the variables of stress, turnover, coping, and self-esteem. Researchers examining organizational effectiveness and management in long-term care have suggested that a participatory collaborative approach to management leads to greater employee satisfaction, performance, less stress and burnout, and improved patient care. The hypotheses tested in this study were that when CNAs and LPNs were included in interdisciplinary team meetings they would have less stress, greater self-esteem, more task-focused coping, and less turnover than those who did not participate in treatment team meetings. Stress was measured by the Care Provider Questionnaire (Mahairas, Oleasrsek, Bristol, Gurule, Kovacs, Peters, Uber, Joyce, Robinson, & Fagan, 1990). Self-esteem was assessed by the Global Self-Esteem Scale (Rosenberg, 1965) and coping was measured by the Multidimensionality of Coping Scale (Endler & Parker, 1990). Turnover was measured through examination of the numbers of individuals leaving the long-term care facility while the study was being conducted. Subjects were randomly assigned to conditions of participation in interdisciplinary treatment team meetings or to a control group. All subjects completed pre-test and post-test assessments. The results were analyzed through analyses of covariance, with the pretest serving as the covariate. Within and between group differences were also evaluated through analysis of variance tests. Correlations between the instruments were assessed through Kendall correlation coefficients. In addition, turnover was examined with Chi Square tests. The statistical analyses suggest that when CNAs and LPNs participate in treatment team meetings, although their levels of self-esteem, stress, and turnover do not significantly change, the amount of task centered coping which they employ is affected by the status of the worker (e.g. CNA or LPN). That is, the impact of being included in a treatment team meeting was more powerful for the lower status worker (CNA) than it was for the worker who had more status (LPN). Several factors such as small sample size, few behavioral measures, and the lack of a treatment control group may compromise the strength of the study. However, several units at the long-term care facility noted that the inclusion of lower status workers led to improved patient care and that they would continue to include CNAs and LPNs in their team meetings in the future. It is suggested that further investigation of this subject examine the variables of unit atmosphere, management style, and leadership style.